The safety of intraocular usage of aspirin. (3rd April 2019) - Dogan, Cezmi; Yetik, Huseyin; Arslan, Osman Sevki; Seymen, Hakki Oktay; Suzer, Oner; Aydin, Ovgu; Mergen, Burak
Abstract: Purpose: To determine the effects of intravitreally injected aspirin on normal ocular tissues. Methods: Six eyes of 3 rabbits as a control group, 18 eyes of 9 albino rabbits which were injected aspirin intravitreally were studied. In the control group, the same volume of balanced salt solution (BSS) as in drug groups were injected. Clinical examination methods including biomicroscopy, indirect ophthalmoscopy, and Schiotz tonometry, electrophysiological test including ERG, and histopathological examination including light microscopy were used to evaluate the ocular effects after drug injections. All the study tests were performed before the injections and 1 week, 1 month, and 3 months after the injections as well. Results: No significant toxicity was determined after injection in terms of the clinical examination methods in all eyes. Cataracts were observed in 27.7% (5/18) of the eyes in the study group. All cataracts in 5 eyes disappeared at the end of three months. In tonometry, no value out of the normal range of rabbits (17.5 ± 3.1 mmHg) was observed. No toxicity sign was observed at electrophysiological and histopathological evaluations. Conclusion: After intravitreal injection of aspirin, no significant toxicity sign was observed other than a reversible cataract. Thus, intravitreal aspirin injections may be an additional or alternative treatment option for several anterior or posterior segment ocular diseases in addition to their topical utilization.